Comparative Analysis of Questions Posed by Hospital-Based Physicians and Physicians Based in the Primary Care Sector. Issue 1 (2nd January 2019) - Davies, Karen
ABSTRACT: Librarians face a wide range of questions from health professionals. The objective of this research was to determine if the types of physicians' information needs (questions) answered by information professionals were affected by the work setting (hospital based or primary sector) of physicians. Librarians and Web sites in the UK that answered clinical information needs collected questions. The questions were reviewed to determine if they were foreground or background and were analyzed using the taxonomy of generic clinical questions. A total of 1, 633 questions were analyzed; 540 from primary care physicians and 1, 093 from hospital-based. The top category was treatment, followed by diagnosis for hospital-sector physicians and management for primary care. Forty percent of the information needs of physicians are background questions that can be answered using basic resources such as medical textbooks. The top three foreground questions accounted for 40% of physicians' information needs.